2020
DOI: 10.1186/s12931-020-1309-2
|View full text |Cite
|
Sign up to set email alerts
|

Gender differences in pulmonary arterial hypertension patients with BMPR2 mutation: a meta-analysis

Abstract: Objective: To investigate the differences in the proportions of BMPR2 mutations in familial hereditary pulmonary arterial hypertension (HPAH) and idiopathic pulmonary arterial hypertension (IPAH) between males and females and the relationship between BMPR2 mutation and PAH severity. Methods: A computer was used to search the electronic Cochrane Library, PubMed/MEDLINE, and EMBASE databases for clinical trials containing information on the relationship between PAH prognosis and BMPR2 mutations through March 201… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 45 publications
4
12
0
Order By: Relevance
“…This was consistent with the meta-analysis data, suggesting that BMPR2 mutation may play a crucial role in the early development of PAH and severe hemodynamic symptoms [7]. Our study also shows that PAH patients were predominantly women (male:female, 1:2.8), although there was no difference in the proportion of BMPR2 mutation carriers, hemodynamic profiles, or death according to sex [32].…”
Section: Discussionsupporting
confidence: 92%
“…This was consistent with the meta-analysis data, suggesting that BMPR2 mutation may play a crucial role in the early development of PAH and severe hemodynamic symptoms [7]. Our study also shows that PAH patients were predominantly women (male:female, 1:2.8), although there was no difference in the proportion of BMPR2 mutation carriers, hemodynamic profiles, or death according to sex [32].…”
Section: Discussionsupporting
confidence: 92%
“…The Registry to Evaluate Early and Long-Term Pulmonary Arterial Hypertension Disease Management (REVEAL) showed a higher female predominance of PAH irrespective of BMPR2 status, and found that the female-to-male ratio for PAH was 3.9:1 in races other than whites, black and Hispanic [21]. Our study results agreed with previous evidence that suggested female dominance in IPAH or HPAH (Table 1) [17].…”
Section: Gene Mutation For Pah Was Associated With Age and Gender Differencesupporting
confidence: 91%
“…The estimated penetrance in male and female carriers is 14% and 42%, respectively [15,16]. It has been shown that female is the single most important determinant for the penetrance of BMPR2 mutations in PAH [15,16]; male patients were significantly more likely to have BMPR2 mutations than female patients [17]. Similarly, in our study, only one male was found to have the BMPR2 mutation.…”
Section: Gene Mutation For Pah Was Associated With Age and Gender Differencesupporting
confidence: 64%
“…BMPR2 carriers with PAH have an earlier disease onset than idiopathic PAH patients [15]. Interestingly, male patients were more likely to possess a BMPR2 mutation than women and develop severe disease in presence of a BMPR2 mutation [16].…”
Section: The Bmpr2 Signaling Pathwaymentioning
confidence: 96%